1976
DOI: 10.1288/00005537-197607000-00011
|View full text |Cite
|
Sign up to set email alerts
|

A new functional approach to the surgical management of pierre robin syndrome: Experimental and clinical report

Abstract: A functional and simple surgical method for treating the respiratory distress of the neonate affected by Pierre Robin syndrome is described. The base of the tongue is placed in an anterior position via a buried wire suture tied around the body of the hyoid. The method proposed in this paper fulfills the following: 1. It is physiologic since the infant is able to suckle and maintain its nutrition by preserving the function of the mobile portion of the tongue for deglutition. 2. Maintenance of the "pushing" acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Hyomandibulopexy (by Bergoin 1971 [27] and by Lapidot 1976 [28]) is designed to anchor the hyoid bone to the mandible anteriorly and to bring the base of the tongue forward. Interference with mandibular growth is considered a drawback of this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Hyomandibulopexy (by Bergoin 1971 [27] and by Lapidot 1976 [28]) is designed to anchor the hyoid bone to the mandible anteriorly and to bring the base of the tongue forward. Interference with mandibular growth is considered a drawback of this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Lapidot et al [83] reported using a stainless-steel wire to wrap around the hyoid bone for the purpose of stabilizing the tongue in an anterior position.…”
Section: Other Surgical Proceduresmentioning
confidence: 99%